Compassion in pediatric oncology: A patient, parent and healthcare provider empirical model. Issue 10 (29th May 2021) - Sinclair, Shane; Bouchal, Shelley Raffin; Schulte, Fiona; M. T. Guilcher, Gregory; Kuhn, Susan; Rapoport, Adam; Punnett, Angela; Fernandez, Conrad V.; Letourneau, Nicole; Chung, Joanna
Abstract: Objective: Compassion has long been considered a cornerstone of quality pediatric healthcare by patients, parents, healthcare providers and systems leaders. However, little dedicated research on the nature, components and delivery of compassion in pediatric settings has been conducted. This study aimed to define and develop a patient, parent, and healthcare provider informed empirical model of compassion in pediatric oncology in order to begin to delineate the key qualities, skills and behaviors of compassion within pediatric healthcare. Methods: Data was collected via semi‐structured interviews with pediatric oncology patients ( n  = 33), parents ( n  = 16) and healthcare providers ( n  = 17) from 4 Canadian academic medical centers and was analyzed in accordance with Straussian Grounded Theory. Results: Four domains and 13 related themes were identified, generating the Pediatric Compassion Model, that depicts the dimensions of compassion and their relationship to one another. A collective definition of compassion was generated– a beneficent response that seeks to address the suffering and needs of a person and their family through relational understanding, shared humanity, and action . Conclusions: A patient, parent, and healthcare provider informed empirical pediatric model of compassion was generated from this study providing insight into compassion from both those who experience it and those who express it. Future research on compassion in pediatric oncology and healthcare should focus on barriers and facilitators of compassion, measure development, and intervention research aimed at equipping healthcare providers and system leaders with tools and training aimed at improving it.